Value For Money Analysis in Measuring the Realization of the Program of the Regional Development Planning Agency (Bapedda) of Medan City in Review from the Islamic Economy - Nurul Wahidah; Sri Sudiarti (Penerbit Jurnal Indonesia, 2022)
This study aims to determine the Value For Money analysis on the realization of the Medan City Regional Development Planning Agency (Bappeda) program. This type of research is descriptive research that focuses on observing the realization of the Medan City Bappeda program through the application of value for money measurements, namely from the point of view of economy, efficiency, and effectiveness. The result of this research is Value For Money analysis which states that the realization of the program from Bappeda Medan City is economical, inefficient, and ineffective. This shows that Bappeda must maximize its performance so that program realization can be carried out properly. Considering that the results obtained are not perfect enough, it is important for the Medan City Bappeda to re-evaluate.